Strategi Manajemen Pendidikan Karakter: Studi Kasus Mamanajemen Pendidikan Karakter Berbasis Agama di SD Al Amin Grogol Sukoharjo 2024/2025 - Sutino, Sutino; Isfihani, Isfihani (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Character building is an important part of forming personality student's personality since an early age. Research This aims to analyze management strategies for education character based on religion at Al Amin Cemani Elementary School, as well as the impact of character development on students. The method used is a qualitative case study. Data collected through interviews with head schools, teachers, and students, as well as observation of activity learning and exploration documents. Research results show that the SD Al Amin management strategy uses the P-O-A-C pattern with optimized educator instruction, guiding, and providing exemplary education to participants, educating with empowering use in a way maximum to the means of the owned school. Impact of management strategy education based on this religion shows on the achievement competence of students in the educational process character. Test results material religious reach score 86.38, education morals noble average Very Good (A), and participants ' ability to memorize part Juz Amma of the Quran. Research recommends the need for schools to complete facilities and infrastructure,e schooasasexpansionn page premises, mosque expansion, additions to bathrooms and toilets, additions and extensions place of abl facilities, procurement of a religious laboratory, and facilities adequate to support the education process at the school. Words: Management Strategy, Character Education, and Religion-Based. Keywords: Management Strategy, Character Education, and Religion-Based